Monitoring near‐miss events in a hospital blood bank. (August 2017) - Karim, F.; Ali, M.; Rashid, A.; Shaikh, M. S.; Karim, M.; Moiz, B.
Abstract : Background and Objective: Monitoring near‐miss events is a part of hemovigilance which helps to identify the causes and prevent them from happening again. The aim was to identify the near‐miss events in a tertiary care hospital and interventions in reducing them. Methods: The study was carried out at the section of Hematology and Transfusion medicine, The Aga Khan University Hospital. Two‐year data of near‐miss events were analysed from January 2013 to December 2014. This was followed by intervention to minimize the errors. Following intervention, rate of wrong blood in tube (WBIT) was monitored for 1 year (January 2016–December 2016). Results: During the study period, a total of 75 157 blood samples were received in blood bank with the request for various blood products and 123 360 blood products were released. The calculated rate of near‐miss events was 0·35 per 1000 blood products issued. WBIT was the most common near‐miss event reported with a rate of 1 in 1789. Monitoring near‐miss events prompted us to intervene to minimize WBIT. Interventions included educational workshops and lectures for nurses and medical doctors, initiation of bedside ABO grouping, making a dedicated phlebotomy station for emergency room, starting online computer physician order entry system for raising blood requests and circulating educational flyers. Following intervention, the rate of WBIT dropped to 1 in 2457 blood samples. Conclusion: Monitoring of near‐miss events helped us in identifying the processes that can be improved and taking appropriate measures to enhance transfusion safety.